Analysis of the Effect of Supervisor Competence on Work Safety Compliance, with Motivation as a Mediating Variable, in Electricity Projects at PT PLN (Persero) Project Management Center - Iqbal Makki; Retno Widyaningrum; Ratna Sari Dewi (Journal of Social Research, 2026)
This study aims to analyze the effects of safety knowledge, safety leadership, and safety attitude on supervisor competence, safety motivation, and safety compliance, as well as to examine the mediating role of safety motivation in the relationship between supervisor competence and safety compliance in power infrastructure projects managed by PT PLN (Persero) Pusat Manajemen Proyek. This study employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through a questionnaire using a six-point Likert scale and distributed to employees and outsourced personnel with at least two years of work experience. Of the 160 questionnaires collected, 126 responses met the predetermined criteria and were included in the analysis. The measurement model evaluation confirmed that all research indicators satisfied the validity and reliability requirements. The results indicate that safety attitude and safety motivation have positive and significant effects on safety compliance, with safety motivation demonstrating the strongest influence. Safety knowledge and safety attitude also have positive and significant effects on safety motivation, while safety leadership does not show a significant effect. Furthermore, safety knowledge and safety attitude positively and significantly influence supervisor competence, with safety knowledge emerging as the most dominant factor. These findings suggest that improving OHS compliance at PLN Pusmanpro should focus on strengthening safety motivation and safety attitude, enhancing practical and job-relevant safety knowledge, and developing supervisor competence and safety leadership through more visible and consistent practices in the field.